Maternal anemia associated with walkable distance to healthy food sources in Bronx, New York. (January 2015) - Bottalico, Danielle M.; Johnson, Glen D.; Chazotte, Cynthia; Karkowsky, Chavi Eve
Highlights: A database of healthy food sources (HFSs) is built for Bronx, New York. Walkable access to an HFS was computed for over 4000 pregnant women. Living within 0.25 miles of an HFS protected against anemia for lower income women. No effect was detected for women who had commercial health insurance. Abstract: The relationship between walkable access to healthy food sources and risk of anemia in pregnancy was evaluated for a cohort of 4678 women who initiated prenatal care in the year 2010 at an academic medical center in Bronx, New York. After geocoding patient residences, street network distances were obtained for the closest healthy food sources, which were identified from multiple databases. For lower-income patients, as indicated by Medicaid or lack of health insurance, those who lived less than 0.25 miles from a healthy food source were less likely to be anemic when compared to those who lived farther (adjusted OR = 0.65, 95% CI 0.48, 0.88). Patients with commercial insurance showed no effect. These results help to understand how a nutritionally-mediated condition such as anemia during pregnancy can be affected by one's built environment, while also highlighting the importance of conditioning on socioeconomic status for these types of studies.